2010
DOI: 10.1128/cvi.00380-09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Psychological Stress and Fluoxetine on Development of Oral Candidiasis in Rats

Abstract: Psychological stress has been found to suppress cell-mediated immune responses that are important for limiting the proliferation of Candida albicans. Fluoxetine has been observed to reduce negative consequences of stress on the immune system in experimental and clinical models, but there are no data on its effects on oral candidiasis. We designed experiments to evaluate the effects of fluoxetine on the development of oral candidiasis in Sprague-Dawley rats exposed to a chronic auditory stressor. Animals were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…(b) The intraoral image of the lesion on the 20th day of the follow-up that was sent by the patient. c. The intraoral image of the lesion on the 40th day at the end of the treatment that was sent by the patient ulcer, the medications, and the contribution of psychological stress to immunosuppression (Núñez, Novío, Suárez, Balboa, & Freire-Garabal, 2010;Rodríguez-Galán et al, 2010), we concluded that the possibility of an atypical oral ulcer inducted by candida infection was high. She was advised to give up complete denture use and stop the local corticosteroid treatment.…”
Section: Reply To Letter To the Editormentioning
confidence: 84%
“…(b) The intraoral image of the lesion on the 20th day of the follow-up that was sent by the patient. c. The intraoral image of the lesion on the 40th day at the end of the treatment that was sent by the patient ulcer, the medications, and the contribution of psychological stress to immunosuppression (Núñez, Novío, Suárez, Balboa, & Freire-Garabal, 2010;Rodríguez-Galán et al, 2010), we concluded that the possibility of an atypical oral ulcer inducted by candida infection was high. She was advised to give up complete denture use and stop the local corticosteroid treatment.…”
Section: Reply To Letter To the Editormentioning
confidence: 84%
“… also found that injection of lipopolysaccharide provoked a significant increase in the circulating levels of corticosterone and alterations in cytokine levels, consistent with dysregulation of the immune system, in an animal model of depression. Psychological stress has been also shown to exacerbate oral infection with the opportunistic pathogen, Candida albicans , in rodents .…”
Section: Influence Of Psychosocial Factors In Periodontitismentioning
confidence: 99%
“…Since psychological stress has been found to suppress cell-mediated immune responses that are important for limiting the proliferation of C. albicans, Núnez et al 54 evaluated the effects of stress on oral candidiasis in rats exposed to a repeated auditory stressor. The results showed that stress exacerbated C. albicans infection in the tongue dorsum of the rats.…”
Section: Models Of Experimental Oral Candidiasis In Ratsmentioning
confidence: 99%